Theory and practice of ethnography : readings from the periphery - Kasi, Eswarappa; Malik, Ramesh C. (Indira Gandhi Rashtriya Manav Sangrahalaya ; Rawat Publications, 2009)
Contributed articles presented at an international conference organized by School of Humanities and School of Social Science, University of Hyderabad in July 3-5, 2007.